Catalyst-free site-specific surface modifications of nanocrystalline diamond films via microchannel cantilever spotting. Issue 63 (15th June 2016) - Davydova, Marina; de los Santos Pereira, Andres; Bruns, Michael; Kromka, Alexander; Ukraintsev, Egor; Hirtz, Michael; Rodriguez-Emmenegger, Cesar
Abstract : Microchannel cantilever spotting is combined with a copper-free click chemistry ligation to achieve the patterning of nanocrystalline diamond films. Abstract : The properties of nanocrystalline diamond (NCD) films offer great potential for the creation of various sensing and photonic devices. A great challenge in order to materialize such applications lies in achieving the micrometrically resolved functionalization of NCD surfaces. In the present work, we introduce a facile approach to meet this challenge employing the novel strain-promoted alkyne–azide cycloaddition "click" chemistry reaction, a catalyst-free ligation protocol compatible with biomolecules. The ability to achieve well-resolved multicomponent patterns with high reproducibility is demonstrated, paving the way for the fabrication of novel devices based on micropatterned NCD films.